Insulin resistance, lipids and body composition in patients with coronary artery disease after combined aerobic training and resistance training: a randomised, controlled trial - Tim Kambic; Mojca Božič Mijovski; Borut Jug; Vedran Hadžić; Mitja Lainscak (Diabetology & Metabolic Syndrome, 2023)
Abstract Background The effect of resistance training (RT) in cardiac rehabilitation (CR) on insulin resistance remains elusive. We examined whether the addition of high-load (HL) or low loads (LL) RT has any effect on the levels of insulin resistance and lipids versus aerobic training (AT) alone in patients with coronary artery disease (CAD). Methods Seventy-nine CAD patients were randomised to HL-RT [70–80% of one repetition maximum (1-RM)] and AT, LL-RT (35–40% of 1-RM) and AT or AT (50–80% of maximal power output), and 59 patients [75% males, 15% diabetics, age: 61 (8) years, left ventricular ejection fraction: 53 (9) %] completed the study. Plasma levels of glucose, insulin, blood lipids [total cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol and low-density lipoprotein (LDL)] cholesterol and body composition were measured at baseline and post-training (36 training sessions). Results Training intervention had only time effect on lean mass (p = 0.002), total and LDL cholesterol levels (both p < 0.001), and no effects on levels of glucose and insulin resistance (homeostatic assessment 2-insulin resistance). Total and LDL cholesterols levels decreased following AT [mean difference (95% confidence interval); total cholesterol: − 0.4 mmol/l (− 0.7 mmol/l, − 0.1 mmol/l), p = 0.013; LDL: − 0.4 mmol/l (− 0.7 mmol/l, − 0.1 mmol/l), p = 0.006] and HL-RT [total cholesterol: − 0.5 mmol/l (− 0.8 mmol/l, − 0.2 mmol/l), p = 0.002; LDL: − 0.5 mol/l (− 0.7 mmol/l, − 0.2 mmol/l), p = 0.002]. No associations were observed between post-training change in body composition and post-training change in blood biomarkers. Conclusions RT when combined with AT had no additional effect beyond AT alone on fasting glucose metabolism, blood lipids and body composition in patients with CAD. Trial registration number NCT04638764.